Cd8+ expression in oral potentially malignant disorders associated with risk factors in selected population of east Indonesia - Irene Tania Bijaya; Firstine Kelsi Hartanto; Rahmi Amtha; Indrayadi Gunardi (Odonto : Dental Journal, 2023)
Background: Oral potentially malignant disorder (OPMD) is a lesion with a high potential to turn into oral squamous cell carcinoma (OSCC). The discovery of OPMD lesions precedes most cases of OSCC. Sensitive and specific biomarkers can help in the early detection of high-risk patients, one of which is CD8+, part of the cytotoxic T lymphocytes, which have a role in eliminating cancer cells. Several studies use infiltration density and CD8+ T cells' activity as biomarkers in malignancy. This study aims to observe the expression of CD8+ in OPMD lesions and correlate with risk factors Method: Twelve paraffin blocks samples consist of OPMD lesions. One oral lichen planus (OLP) as the positive control. Samples were stained using HE to observe the degree of dysplasia and immunohistochemistry to observe the expression of CD8+ T cells. Observation of results using a microscope with 100x magnification to select the field of view and 400x magnification to count the number of positive CD8+ T cells with a cut-off point of 500 cells from a total of 5 fields of view and determined by weak intensity (